2010
DOI: 10.1007/s10163-009-0284-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of leachate irrigation on methane oxidation in tropical landfill cover soil

Abstract: The effect of leachate irrigation on methanotrophic activity in sandy loam-based landfi ll cover soil with vegetation was investigated. Laboratory-scale experiments were conducted to investigate the methane oxidation reaction in cover soil with and without plants (tropical grass). The methane oxidation rate in soil columns was monitored during leachate application at different organic concentrations and using different irrigation patterns. The results showed that the growth of plants on the fi nal cover layer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…Regional settlements are widely scattered, there are financial constraints and there are objections from nearby settlers 1. Several studies have been conducted dealing with the generation and treatment of leachate 2–9. The presence and treatment of hazardous materials in leachate like heavy metals and volatile organic compounds which may escape into surrounding water bodies like rivers have also been studied 10–14.…”
Section: Introductionmentioning
confidence: 99%
“…Regional settlements are widely scattered, there are financial constraints and there are objections from nearby settlers 1. Several studies have been conducted dealing with the generation and treatment of leachate 2–9. The presence and treatment of hazardous materials in leachate like heavy metals and volatile organic compounds which may escape into surrounding water bodies like rivers have also been studied 10–14.…”
Section: Introductionmentioning
confidence: 99%
“…To cope with this constraint, salt-tolerant vegetation should be used, and the optimum leachate loading should be provided to sustain CH 4 oxidation in landfill operation (Humer and Lechner, 2000). Chiemchaisri et al (2010) also reported beneficial effect of plants on landfill cover provided that leachate loading was properly controlled.…”
Section: Enhancement Of Methane Oxidationmentioning
confidence: 93%
“…Furthermore, this operation is advantageous in reducing leachate concentration and pollutant loading from the landfill. Chiemchaisri et al (2010) studied the effect of leachate irrigation on methane oxidation in tropical landfill cover soil and reported that methane oxidation rate could be enhanced by providing optimal nutrients through leachate irrigation. Intermittent application and controlled organic loading onto the cover soil are the key factors leading to improved microbial activities.…”
Section: Enhancement Of Methane Oxidationmentioning
confidence: 99%
“…High rainfall intensity significantly affects the increasing moisture content in solid waste subsequently in a higher volume of landfill leachates [3]. Because the discharge standard is becoming more and more stringent, which requires advance treatment alternatives for leachates, a combination of physical-chemical and biological methods is essential for the efficient treatment of a leachate [4]. Because there are fewer limitations for membrane technology for high organic loading waste treatment [5], in this study, the Inclined Tube Membrane Bioreactor-Reverse Osmosis process or the itMBR-RO was designed to be applied to treat the high strength of leachates such as a fresh leachate from newer landfills and seepage leachate found in waste transfer stations, known as some of the most concentrated organic wastewater [5].…”
Section: Introductionmentioning
confidence: 99%